Rationality, hermeneutics, and communicational processes: On L. Lachmann's approach of hermeneutical economics - Birger P. Priddat (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2012)
Only a few economists knew about hermeneutical economics. But my request is to confirm hermeneutical economics only for the reason to make it criticable. Without any doubt, hermeneutical economics is worth to be criticized; but it is an incomplete approach. The first part presents Ludwig M. Lachmann's version of hermeneutical economics. Lachmann is picked up from the scenario of hermeneutical economists (i.e. Ebeling, Berger, Lavoie, some authors of Kirzner 1986, etc.), because he is the most prominent one of this small group. His approach is more typical than original, but a profound basement for our handling with the rationality-problem in economics. The second part analyzes some critical issues of this approach, touches some methodological problems, and ends with some helpful reasoning on the relation of hermeneutics and economics.
Keywords: 330